Tests, simulations and web crippling design of S690 and S960 high strength steel unlipped channel sections under end-one-flange loading - Lan, Xiaoyi (2024)
This paper presents experimental and numerical investigations into the web crippling behaviour and structural design of high strength steel unlipped channel sections under end-one-flange loading. An experimental programme including six grade S690 and four grade S960 steel test specimens was firstly carried out, and the corresponding test set-up, procedures and results were reported. The web crippling test results were subsequently used in a finite element programme to validate developed finite element models, which were then adopted to perform parametric studies to cover wider parameter ranges of the bearing length, web slenderness and inside bend radius. It is found that the ultimate web crippling strength of high strength steel unlipped channel sections increases with increasing bearing length but decreasing web slenderness and inside bend radius. Considering that relevant codified design provisions are absent, the design rules of normal strength steel unlipped channel sections, as prescribed in EN 1993-1-3, EN 1993-1-5 and AISI S100, were assessed for their suitability to high strength steel unlipped channel sections. The codified design methods provide inaccurate and scattered resistance predictions for high strength steel unlipped channel sections under end-one-flange loading. Thus, an improved AISI S100 design method and a novel slenderness-based design method were proposed, which can outperform the codified design methods.